The anti-tumor effects of cordycepin-loaded liposomes on the growth of hepatoma 22 tumors in mice and human hepatoma BEL-7402 cells in culture. (1st September 2016) - Wu, Peng-Kai; Tao, Zhi; Ouyang, Zhao; Cao, Jiang-Ye; Geng, Di; Liu, Jin; Wang, Chun-Mei
Abstract: Liposomes have successfully been used for decades to encapsulate and protect drugs that are prone to deactivation in the body. The present study aimed to demonstrate the use of liposomes to encapsulate cordycepin, an adenosine analog that quickly loses its activity in vivo . The cordycepin-loaded liposomes were prepared by the ammonium sulfate gradient approach, and its in vitro and in vivo antitumour activities were evaluated using BEL-7402 cells and hepatocellular carcinoma H22 transplanted tumors, respectively. An MTT assay was used to observe the cytotoxicity of cells treated with cordycepin and cordycepin-loaded liposomes in vitro . High-content screening (HSC) was carried out using Hoechst 33342 to detect apoptotic cells and the ratio of cells in different cell cycle stages. The data demonstrated that both the cordycepin and the cordycepin-loaded liposomes resulted in clear cytotoxicity with IC50 values of 18.97 and 29.39 μg/mL, respectively. The latter showed significantly strong inhibitory effects on H22 tumor growth in mice, while the former did not show any inhibitory effects on tumor growth. In addition, the HSC assay showed that the cordycepin-loaded liposomes resulted in a higher rate of apoptosis than the cordycepin alone in BEL-7402 cells. Further data analysis revealed that the cells treated with cordycepin-loaded liposomes were predominately arrested at the G2/M phase ( p  < 0.05), while those treated with cordycepin alone were arrested in the G0/G1 phase ( p  < 0.05). In conclusion, these results suggest that liposomes can enhance and maintain the in vivo anti-tumor activity of cordycepin.